Evaluation of a Trabecular Micro-Bypass Stent in Pseudophakic Patients With Open-Angle Glaucoma. Issue 11 (November 2016) - Ferguson, Tanner J.; Berdahl, John P.; Schweitzer, Justin A.; Sudhagoni, Ramu
Abstract : Purpose of the Study: The purpose of the study was to evaluate the safety and efficacy of the iStent Trabecular Micro-Bypass stent in pseudophakic patients with open-angle glaucoma. Methods: Retrospective, consecutive case series from October 2012 to May 2015 with no exclusion criteria. The series comprised 42 pseudophakic eyes with open-angle glaucoma that were implanted with 1 iStent. Data were collected preoperatively, and postoperative data were collected at 1 day, 1 week, 1, 3 and 6 months, 1 year, 18 months and 2 years. Data included intraocular pressure (IOP), number of glaucoma medications, the incidence of postoperative IOP pressure spikes ≥15 mm Hg at any timepoint, and the need for additional surgery. Results: The mean preoperative IOP was 20.26±6.00 mm Hg. At 1 year postoperatively, the mean IOP was 16.34±3.78 mm Hg ( P <0.01). At 2 years postoperatively, the mean IOP was 13.62±4.55 ( P <0.01). The mean number of glaucoma medications was 1.95±1.01 preoperative and 1.69±1.28 ( P >0.05) at 1 year postoperatively. Postoperatively, 3 eyes (7%) experienced an IOP increase of 15 mm Hg above their baseline IOP that responded to topical therapy. In total, 96% of patients with an IOP≥19 mm Hg achieved a reduction in IOP at their last collected follow-up. Conclusions: The insertion of the iStent Trabecular Micro-Bypass stent effectively lowers IOP in pseudophakic patients with open-angle glaucoma. Although medication use was not significantly reduced postoperatively at 1 year, 80% of patients either experienced a reduction or no change in medication use. The safety profile appears favorable with a low rate of IOP spikes and only 1 patient requiring additional surgery.